Debye-Waller factor of Pt in X-ray absorption fine structure analyzed using classical anharmonic correlated Einstein model - Huy Thao, Nguyen; Nguyen Thi Minh, Thuy; Viet Hoang, Le; Sy Tien, Tong (Communications in Physics, 2025)
An analysis of the Debye-Waller (DW) factor in the anharmonic X-ray absorption fine structure (XAFS) of crystalline platinum (Pt) has been conducted under the influence of thermal disorder. This factor was calculated in explicit and simple forms from the calculation model developed using the anharmonic effective potential and classical statistical theory based on the correlated Debye model. The thermodynamic parameters of Pt have considered the influence of nearest neighbors on the backscattering and absorbing atoms. The numerical results of the Pt at temperatures from 0 to 800 K fit well with those obtained from the experimental data and other methods. The obtained results indicate that the present calculation model can efficiently investigate the anharmonic XAFS DW factor of Pt.